Analysis Of The Effect Of Pull And Push On Entrepreneurial Motivation (Survey on Instagram Business account users) - Fauziah, Wulan; Maulani, Galih Abdul Fatah; ., Isnawati (Entrepreneurship Faculty, Universitas Garut, 2025)
-Entrepreneurial intent is the desire or motivation of an individual to become an entrepreneur and start a business or venture. Among various age groups, Indonesia's Gen Z generation is known to have an interest in entrepreneurship that is below the average at 1.60% of 18.94%. To increase entrepreneurial interest among Gen Z, an approach is needed, as well as the creation of an environment that develops entrepreneurial potential. This study used a survey distributed online and in person to 115 randomly selected respondents, with a response rate of 50.4%, and 73 responses were recorded. However, only 58 respondents provided varied assessments and met the sampling criteria. The analysis technique used regression through SPSS. The results showed that perceived behavioral control has a significant and positive effect on entrepreneurial intention, with an R value of 0.416 and R² of 0.173 (17.3% influence), and a significance value of 0.001 < 0.05, indicating strong predictive power. In contrast, subjective norms did not significantly affect entrepreneurial intention, as shown by a significance value of 0.22. However, when combined, perceived behavioral control and subjective norms jointly have a significant effect, with an R value of 0.477 and R² of 0.143. These findings highlight that increasing perceived control over entrepreneurship is key to boosting entrepreneurial intention among Indonesia’s Gen Z.